Composition, Growth, Succession, and Function in the Cladophora Microbiome: Insights From Quantitative Stable Isotope Probing and NanoSIMS Imaging - Raina M. Fitzpatrick; Bruce A. Hungate; Mary Power; Megan Foley; Ty Samo; Egbert Schwartz; Micheala Hayer; Peter K. Weber; Jennifer Pett‐Ridge; Jane C. Marks (Environmental Microbiology, 2025)
The branching green macroalga Cladophora glomerata and its epiphytic microbiome dominate summer biomass in the Eel River, a Northern California river under Mediterranean (summer drought, winter rain) seasonality. Green Cladophora streamers proliferate in early summer, then change to yellow and then red‐brown as epiphyte loads increase. We characterised successional changes in epiphytic bacteria on Cladophora , examining both community composition and growth rates, using quantitative Stable Isotope Probing (qSIP) and 16S rRNA gene amplicon sequencing. The number of bacterial taxa increased with succession while growth rates peaked in the middle stage. NanoSIMS imaging confirmed high sulphur (S) concentrations in Cladophora cell walls relative to surrounding biomass, coinciding with a bloom of sulphur bacteria (bacteria that reduce or oxidise sulphur/sulphates). In general, relative abundances and growth rates were independent, indicating that either metric alone is insufficient for understanding how taxonomy and functional groups affect ecosystem processes. For instance, the relative abundance of nitrogen fixers peaked in the late summer when their relative growth rates were slowest. Such patterns may be driven by space competition limiting growth. Together, changes in abundance and relative growth rates suggest different limiting factors for different functional groups in the Cladophora microbiome at multiple successional stages.

The algal microbiome protects Desmodesmus intermedius from high light and temperature stress - Ty J. Samo; Kristina A. Rolison; Courtney J. Swink; Jeffrey A. Kimbrel; Suzan Yilmaz; Xavier Mayali (Algal Research, 2023)

Attachment between heterotrophic bacteria and microalgae influences symbiotic microscale interactions - Ty J. Samo; Jeffrey A. Kimbrel; Daniel J. Nilson; Jennifer Pett‐Ridge; Peter K. Weber; Xavier Mayali (Environmental Microbiology, 2018)
Summary The surface and surroundings of microalgal cells (phycosphere) are critical interaction zones but have been difficult to functionally interrogate due to methodological limitations. We examined effects of phycosphere‐associated bacteria for two biofuel‐relevant microalgal species ( Phaeodactylum tricornutum and Nannochloropsis salina ) using stable isotope tracing and high spatial resolution mass spectrometry imaging (NanoSIMS) to quantify elemental exchanges at the single‐cell level. Each algal species responded differently to bacterial attachment. In P. tricornutum , a high percentage of cells had attached bacteria (92%–98%, up to eight bacteria per alga) and fixed 64% more carbon with attached bacteria compared to axenic cells. In contrast, N. salina cells were less commonly associated with bacteria (42%–63%), harboured fewer bacteria per alga, and fixed 10% more carbon without attached bacteria compared to axenic cells. An uncultivated bacterium related to Haliscomenobacter sp. was identified as an effective mutualist; it increased carbon fixation when attached to P. tricornutum and incorporated 71% more algal‐fixed carbon relative to other bacteria. Our results illustrate how phylogenetic identity and physical location of bacteria and algae facilitate diverse metabolic responses. Phycosphere‐mediated, mutualistic chemical exchanges between autotrophs and heterotrophs may be a fruitful means to increase microalgal productivity for applied engineering efforts.

Corrigendum: Broad distribution and high proportion of protein synthesis active marine bacteria revealed by click chemistry at the single cell level - Ty J. Samo; Steven Smriga; Francesca Malfatti; Byron P. Sherwood; Farooq Azam (Frontiers in Marine Science, 2014)

Broad distribution and high proportion of protein synthesis active marine bacteria revealed by click chemistry at the single cell level - Ty J. Samo; Steven Smriga; Francesca Malfatti; Byron P. Sherwood; Farooq Azam (Frontiers in Marine Science, 2014)